(3QSGdI aj GdJTHjgGJs - (3CHh GdKfGA Hf GdTgGH eMehOs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO agPg QSGdI dWjaI ai GdJTHjgGJ CPcQ ajgG YOOgG CYde Cf GdJTHjg gh GdOdGdI Ydi ETJQGc s
(3BNQgG (B:s
(3hce ef Tbjb bGd eGdc hGLekG abdJ JQi eG Hi hJSCdfi eGdi Je cJGH GdJTHjgGJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdYHGSjI (B- (3NRGfI Bd HGTf CYjGf GdHUQI (B(26 (3C(B) s
Keywords: (3GdeLGejYs